Narcotrafic, conflit armé et sécurité : une perspective à partir du cas colombien - Ricardo Vargas Meza (L'Ordinaire des Amériques)
Amidst domestic war, narcotrafficking has produced long-term transformations in Colombia’s economy and political culture. Its symbiotic embeddedness within large economic and political interests has led profoundly redefined the agrarian structure nationwide, leading to more inequality, and to the formation of a group of rentier landowners who are developing intensive forms of cattleranching. Simultaneously, large parts of the territory are now dominated by illegal security organizations, heirs to the mafia. The drug trade has helped finance both anti-insurgency movements and the guerilla. In this light, all claims of success in the fight against narcotrafficking – such as those uttered by official sources – must be viewed with skepticism.